Images, writing and form: messages that complement each other on Funerary Monuments and Instrumentum Domesticum demonstrated by examples from the north-Western provinces (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The communication media of images, writing and form could be combined into an overall message on one object. These media were given different weight and emphasis according to the intention of the message. In this study funerary monuments and so-called small inscriptions (Inscriptions on everyday objects) were chosen as examples of these media combinations. Funerary monuments show regional preferences that seem to reflect different societal dispositions and  values, perhaps not on a case by case basis   but definitely in a comparison between provinces: the Gallic and Germanic provinces relied mainly on form and images, provinces along the Danube mainly on writing/inscriptions. Small inscriptions also feature combinations of communication media (i.e. the fibula from Inheiden), however they primarily provide an abundant field of research for the interactions between different media. This is illustrated on the basis of complementary distribution patterns.
Keywords: Grave Monuments; Votives; Jupiter-columns; Fibulae; Small inscriptions; Instrumentum Domesticum